Study of Analytical Characterization and Antibacterial Activity of Silver Nanoparticles Synthesized by Using Pineapple Juice as a Reducing Agent - Wahran M. Saod1 , Dhelal Abdul Ghafoor2 , Laith M Najeeb3, Mohammed J. Mansoor Al-Taee4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In the past years, various phytosynthetic processes have been utilised of silver nanoparticles for the low cost and environmentally friendly comparing to the chemical and physical methods. These unique metal nanoparticles are used in several applications which are including pharmaceuticals, antimicrobial and biomedical applications. Wherefore, the object of this work is biosynthesizing AgNPs from extracts of pineapple juice as reducing studying their characteristics by Ultraviolet-Visible (UV-vis) Spectrometer, Atomic Force Microscope (AFM), SEM Scanning Electron Microscope and Transmission Electron Microscope (TEM) The UV-Vis spectra results show a strong resonance centered on the surface of silver nanoparticles (AgNPs) at 410 nm. the presenting study is involved the preparation of (AgNPs) from natural source, which confirmed by UV-Visible spectral analysis in 410nm and the synergism effects with some antibiotic to increase the sensitivity to some pathogenic bacterial isolate as E. coli. In addition, our study is presented results of the minimum inhibitory concentration (MIC) that MIC for AgNPs is 25 while other antibiotics are (32,64,128). Finally, the synergism activity shows a significant difference in the sensitivity of some antibiotics used against E. coli bacteria, especially with levofloxacin and increased the inhibition form 419 mm to 1657.2 mm.